TAUHID DALAM PENDIDIKAN ISLAM MENURUT MUHAMMAD ABDUH DAN RASYID RIDHA - Asep Muqofi (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
The purpose of this research is 1) the value of tawheed in education according to Muhammad Abduh; 2) the value of tawheed in education according to Rasyid Ridha; 3) the equation and difference in the value of monotheism in Islamic education according to Muhammad Abduh and Rasyid Ridha. The research method used is library research research (library research). The primary data source in this study is the Book of Tafsir al Manar by explaining the thought of learning Tawheed from two influential figures, while the secondary data in this study are books, journals, papers, articles or other sources that do not discuss directly but still have something to do with this research. The findings of this study, according to the two figures, that thinking rationally in achieving a misfortune must be adjusted to the current situation so that new interpretations by opening the door of ijtihad, instilling noble morals, clean souls, accompanied by high education can make faith stronger, form The mindset of a child who gives birth to positive behavior while at the same time realizing a pious person who will achieve happiness in the afterlife, this will form a person who has a balanced mental structure that not only emphasizes the development of reason but also spiritual development so that signs of the greatness and oneness of God materialized and integrated.